Pratiques agropastorales et modes de patures des bovins dans la zone subhumide du Nigeria - Bayer, W. (1986)
Examines the consequences for cattle husbandry of livestock-crop integration as practiced in an agropastoral production system in the sub-humid zone of Nigeria - based on a study of herding practices and cattle grazing behaviour.